Relationships among sex, sexual orientation, dark triad traits, sociosexuality, and sexual excitation/inhibition - Semenyna, Scott W.; Vasey, Paul L.; Honey, P. Lynne (My University, 2025)
Subclinical narcissism, psychopathy, and Machiavellianism are a cluster of manipulative, callous, and entitled traits known as the Dark Triad (DT). These traits have been repeatedly linked to short-term mating strategies and a tolerance for uncommitted sexual behavior (i.e., unrestricted sociosexuality) in both men and women, a pattern interpreted as consistent with life history theory. Alongside sociosexuality, individuals vary in their distinct capacities toward sexual excitation and sexual inhibition. Although much research has examined the relationships between DT traits and sociosexuality, and between sociosexuality and sexual excitation/inhibition, none has simultaneously evaluated the links among all three. In a large undergraduate sample, DT traits and sexual excitation/inhibition showed unique multivariate associations with sociosexuality, even when accounting for age, sex, relationship status, and sexual orientation. Results suggest that DT traits, elevated sexual excitation, lower inhibition and bisexuality, facilitate fast life history strategies in both males and females.
Keywords: sociosexuality; Dark Triad (DT); sexual behavior